The role of community compensation mechanisms in reducing resistance to energy infrastructure development - Marie Hyland; Valentin Bertsch (The Economic and Social Research Institute (ESRI), 2017)
Across the EU, significant investments are being made in renewable generation and grid technologies, however, policy makers and planners are frequently met with resistance from local communities to proposed infrastructure development. Offering some form of compensation to the affected communities may reduce objections and minimise project delays. While there are numerous methods of compensating and involving local communities, evidence on which methods are most effective at increasing acceptance of infrastructure developments is scant. We therefore carry out a nationally-representative survey of Irish citizens to analyse how different compensation methods affect acceptance. Ireland is a useful case study because of its high RES-E targets. Respondents are presented with four compensation models for the local construction of a wind farm, and two for the local development of the transmission grid. While it is often reported that communities would prefer deeper levels of involvement, we find no evidence of this. Instead, we find a preference for schemes in which people receive financial compensation without sharing in the ownership and associated risks of project development. Our econometric analyses show that certain socio-demographic characteristics, for example, age and income are significant predictors of people's acceptance under different schemes, while a person's education level significantly predicts whether a particular compensation scheme will increase acceptance. Moreover, we find that the satisfaction with local planning procedures and the tradeoff people make between environmental sustainability and economic competitiveness consistently affect people's attitudes. Such evidence can help policy makers better understand and design policies to minimise resistance to energy infrastructure development.
Keywords: 330; renewable energy; grid expansion; Social acceptance; community compensation; community engagement